El papel del derecho comunitario andino en la temática del medio ambiente desde las competencias de los municipios (2021)
Taking into account the importance of the relationship generated between the four legal systems of Andean Community (CAN) and, of course, of Colombia from the correct application of public policies that promote the protection and conservation of the environment by the municipalities, this article aims to highlight the role of Andean Community law in the environmental issues from the authority of the municipalities. Therefore, this article develops the following topics: 1) the legal nature of Andean Community law; 2) what is Andean Community law for and why does it exist? 3) The regulatory framework of the Andean Community (CAN) and Colombia regarding the environment in the municipalities, and 4) the role, importance and purpose of the Andean Community law with regards to the environment in relation to municipalities. Consequently, the research problem posed is based on the following question: does the role of Andean Community law in environmental issues seek to generate positive or negative impact from the authority of the municipalities? To this effect, it is considered that the regulatory framework of the municipalities does not attend the supranational decisions of the CAN from the environmental perspective.